Analysis Characteristics of Passenger in Election of Executive Ship Transportation Mode (Cases Study: Bakau Heni-Merak Port) - Atika Ulima Zhafira; Rahayu Sulistyorini; Kristianto Usman (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
Ferry is one of the strategic water transportations, but Ferry is often not considered important in its development, so research are needed to examine the effect of passenger characteristics on executive ferry transportation. Mode selection is one of the models used in transportation planning, this is due to the key role of public transportation in an effort to improve services from transportation modes. This study was conducted to determine the characteristics and factors that influence passengers in choosing modes. The analysis of the mode selection model in this study uses logistic regression analysis with the help of the SPSS program. The results in the study explain that the factors that influence the choice of mode for executive ferry passengers are Income Level Variables (X5), Transportation to Port Variables (X7) and Ship Schedule Considerations Variables (X10). Results Based on statistical tests, the following logistic regression was obtained: Y = 0.049 + 1.593 X5 + 1.017 X7 + 0.0834 X10